GE_GERICHTE C/3215/2012 vom 24. November 2014 - GE Cour de justice (2014)
SOCIÉTÉ COOPÉRATIVE D'HABITATION; SORTIE; EXPULSION DE LOCATAIRE; BRUIT; RESPECT; VOISIN | CO.846.3; CO.271; CO.271.1; CO.272.1; CO.272b.l